Contents and Forewords of MIMBAR PENDIDIKAN Journal, Issue of September 2019 - MIMBAR PENDIDIKAN, Editor Journal (MIMBAR PENDIDIKAN, 2019)
MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan (Indonesian Journal for Educational Studies) This journal, with ISSN 2527-3868 (print) and 2503-457X (online), was firstly published on March 11, 2016, by UPI (Indonesia University of Education) Press in Bandung and orgnized by the Lecturers of UPI Journal Developer Team. The MIMBAR PENDIDIKAN  is a new version journal from the old journal with the similar name that was published since 1995 to 2005. This journal is dedicated not only for Indonesian scholars who concern about educational studies, but also welcome to the scholars of Southeast Asian countries and around the world who care and share related to the educational studies in general. The MIMBAR PENDIDIKAN journal is published twice a year i.e. every March and September.Bandung, Indonesia: September 30, 2019 Prof. Dr. H.R. Asep KadarohmanHonorable Patron of MIMBAR PENDIDIKAN Journal; and Rector of UPI, Indonesia University of Education, in Bandung, West Java, Indonesia. E-mail: kadar@upi.edu